Racial inequality in mathematics education : exploring academic identity as a sense of belonging - Elin-Saintine, Thierry (Studies in educational ethnography., 2021)
This book focuses on the math identity construction of 11 Black students. High school students' perception of what/who is a math person constrained and limited their sense of belonging to the community of doers of mathematics. This study offers new insights into the racial opportunity-gap in mathematics education.